2023
DOI: 10.1021/acs.iecr.2c04350
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Weathering and Corrosion Resistance of Eu-Doped ZnO Solid Solution Material by Fluorescence Modification

Abstract: Influencing the electrochemical properties of materials by modulating luminescence is a fascinating topic. It was found that the corrosion protection of the material could be enhanced by fluorescence. Utilizing the fluorescence of the material, the energy of the photons entering the system is reduced, thereby increasing the durability of the coating. The experimental results showed that the europium-doped zinc oxide solid solution (ZEOSS) composite shielding layer has good weathering resistance. The corrosion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the Bode plots in Figure c,d, the phase angle in the high frequency region (10 4 to 10 5 Hz) indicates the protective capacity of the composite coating . The higher the phase angle, the greater is the corrosion protection . In comparison with the WO 3 and pure epoxy coatings, the phase angle of the VW composite coating tended to move toward higher frequencies (10 4 → 10 5 Hz), thereby indicating that the VW composite coating was more hydrophobic, which provides more comprehensive protection to the iron substrate and significantly improves the corrosion protection of the coating.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the Bode plots in Figure c,d, the phase angle in the high frequency region (10 4 to 10 5 Hz) indicates the protective capacity of the composite coating . The higher the phase angle, the greater is the corrosion protection . In comparison with the WO 3 and pure epoxy coatings, the phase angle of the VW composite coating tended to move toward higher frequencies (10 4 → 10 5 Hz), thereby indicating that the VW composite coating was more hydrophobic, which provides more comprehensive protection to the iron substrate and significantly improves the corrosion protection of the coating.…”
Section: Resultsmentioning
confidence: 97%
“…27 The higher the phase angle, the greater is the corrosion protection. 28 In comparison with the WO 3 and pure epoxy coatings, the phase angle of the VW composite coating tended to move toward higher frequencies (10 4 → 10 5 Hz), thereby indicating that the VW composite coating was more hydrophobic, 29 which provides more comprehensive protection to the iron substrate and significantly improves the corrosion protection of the coating. The contact angle test is shown in Figure 5.…”
Section: Anticorrosion Performancementioning
confidence: 97%
“…In comparison with pure epoxy resin coating, the corrosion potential ( E corr ) of the ZCNs coatings shifted toward the cathodic region, suggesting that the ZCNs coatings have cathodic protection . Corrosion current density ( I corr ) is an important parameter for determining the corrosion rate, and low corrosion current density indicates that the coating has high corrosion resistance . The corrosion current density was calculated by using Tafel extrapolation (Figure d).…”
Section: Resultsmentioning
confidence: 99%
“…28 Corrosion current density (I corr ) is an important parameter for determining the corrosion rate, and low corrosion current density indicates that the coating has high corrosion resistance. 29 The corrosion current density was calculated by using Tafel extrapolation (Figure 5d). The corrosion efficiency was calculated from eq 5.…”
Section: Anticorrosion Performancementioning
confidence: 99%
“…Europium (Eu), the seventh element of the Ln series, is the most reactive metal, having reactivity equal to calcium and the lowest density as compared to other elements of the Ln series. Eu plays a vital role in various fields due to its luminosity, and it has been used in display technologies, biomedical science, and anticounterfeiting technology. Zhao et al found that Eu atoms having a high energy conversion rate increased the band gap of ZnO by providing additional energy levels, and thus improving the properties of ZnO. Moreover, the corrosion testing revealed that this variation in electronic structure, 9 times increased the corrosion inhibition efficiency.…”
Section: Applications and Prospects Of Ln Elementsmentioning
confidence: 99%